Online Political Activism by Opposition Political Parties against Government’s Policy during Crises in Cameroon: A Functional Analysis of the Social Democratic Front (SDF) Party during the Anglophone Crisis Of 2016 (African Journal of Law and Politics, 2023)
At the dawn of this digital era, political parties have increasingly incorporated Information and Communication Technologies (ICTs), such as the internet into their political communication strategies both in peace times and during crises situations. The crisis in question here is the Anglophone Crisis of 2016 in Cameroon. This is a crisis which began in the North West and South West Regions from 2016 as a consequence of a series of strike actions and demonstrations orchestrated by the Common Law Lawyers and English speaking teachers trade unions in what they described as their marginalized state in a predominantly French Cameroon. Using the Functional Discourse Theory as an analytical tool, it is glaring that during this crisis, the SDF Party, whose fief is in these regions exploited this situation to its advantage by using the internet to popularize diverse messages. These messages, which ranged from the party’s “acclaimation” of the crisis, its “attack” on government’s policy, and to its “defensive” action in favour of its federalist agenda as the only panacea out of this crisis, were all manifest measures aimed at checking government’s policy. Hence, this write up recommends that it is relevant for the government to always develop the political will of integrating opposition political parties like the SDF in its policy making in times of crisis. This is explained by the fact that this crisis which began peacefully has for more than four years today metamorphosed into an armed conflict between government forces and Anglophone separatist armed groups due partly to government’s inability to manage it by working in synergy with key political opposition actors, such as the SDF Party in seeking lasting solutions.